2008
DOI: 10.2174/187221408784534240
|View full text |Cite
|
Sign up to set email alerts
|

The Follow-Up of Dietary Treatment of Obesity

Abstract: Obesity is a disease with an acknowledged high metabolic and cardiovascular risk, however, only recent studies demonstrated that the dietary treatment of obesity consisting of lifestyle modification programs may be successful in the long run. As for any therapeutic procedure, the dietary hypocaloric treatment of obesity has results and objectives to be verified and surveillance is needed as far as it concerns safety and tolerability. The epidemic of obesity is spreading to impressive levels in the western worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Nonsurgical management of obesity often involves a cognitive‐behavioral approach (3,4) aimed at changing unhealthy lifestyles, adopting a healthy dietary model, and increasing regular physical activity. Clinical studies have demonstrated that nonoperative treatments for obesity aimed at maintaining a stable body weight can prevent obesity‐related comorbidities (5).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsurgical management of obesity often involves a cognitive‐behavioral approach (3,4) aimed at changing unhealthy lifestyles, adopting a healthy dietary model, and increasing regular physical activity. Clinical studies have demonstrated that nonoperative treatments for obesity aimed at maintaining a stable body weight can prevent obesity‐related comorbidities (5).…”
Section: Introductionmentioning
confidence: 99%